Purification and partial characterization of lactacin F, a bacteriocin produced by Lactobacillus acidophilus 11088. - Muriana, P M (1991)
Lactacin F, a bacteriocin produced by Lactobacillus acidophilus 11088 (NCK88), was purified and characterized. Lactacin F is heat stable, proteinaceous, and inhibitory to other lactobacilli as well as Enterococcus faecalis. The bacteriocin was isolated as a floating pellet from culture supernatants brought to 35 to 40% saturation with ammonium sulfate. Native lactacin F was sized at approximately 180 kDa by gel filtration. Column fractions having lactacin F activity were examined by electron microscopy and contained micelle-like globular particles. Purification by ammonium sulfate precipitation, gel filtration, and high-performance liquid chromatography resulted in a 474-fold increase in specific activity of lactacin F. The purified bacteriocin was identified as a 2.5-kDa peptide by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The lactacin F peptide retained activity after extraction from SDS-PAGE gel slices, confirming the identity of the 2.5-kDa peptide. Variants of NCK88 that failed to exhibit lactacin F activity did not produce the 2.5-kDa band. Sequence analysis of purified lactacin F identified 25 N-terminal amino acids containing an arginine residue at the N terminus. Composition analysis indicates that lactacin F may contain as many as 56 amino acid residues.